(untitled) (E Conference Zone, 2022)
This article mainly focuses on the topic teaching reading to learners of B 2 level on the basis of authenticity. Teaching reading skill is an essential part in teaching language as a whole. Moreover, the article dwells on the application of authentic materials in the process of teaching reading.